Screening of chilies for pesticide residues / Ummu Salamah Ismail - Ismail, Ummu Salamah (Faculty of Applied Sciences, 2009)
The aim of this study was to investigate pesticide residues in three types of market chilies in Shah Alam. A total of six samples of chilies from two favorable food stock sources of UiTM community were analyzed. Pesticide residues were screened by gas chromatography with mass spectrometry. In 1 of the samples no residues were found, three of samples contained two types of pesticide residues, two of samples contained two types of pesticide residues and one of the samples contained five types of pesticide residues. Most frequently found pesticide were Bis(2-ethlhexyl)phthalate (found in three samples) and phenol,2-methoxy (found in two samples). This findings of this study pointed to the following recommendations of need for monitoring program for pesticide residues in vegetables especially imported food crops.